Microbiological quality of drinking water of urban and rural communities, Brazil Qualidade microbiológica de água potável de comunidades urbanas e rurais, Paraná - Giovani Nogueira; Celso V Nakamura; Maria CB Tognim; Benício A Abreu Filho; Benedito P Dias Filho (Universidade de São Paulo, 2003)
OBJECTIVE: To evaluate the microbiological quality of treated and untreated water samples came from urban and rural communities and to examine the relationship between coliforms occurrence and average water temperature, and a comparison of the rainfall levels. METHODS: A sample of 3,073 untreated and treated (chlorinated) water from taps (1,594), reservoir used to store treated water (1,033), spring water (96) and private well (350) collected for routine testing between 1996 and 1999 was analyzed by the multiple dilution tube methods used to detect the most probable number of total and fecal coliforms. These samples were obtained in the region of Maringá, state of Paraná, Brazil. RESULTS: The highest numbers water samples contaminated by TC (83%) and FC (48%) were found in the untreated water. TC and FC in samples taken from reservoirs used to store treated water was higher than that from taps midway along distribution lines. Among the treated water samples examined, coliform bacteria were found in 171 of the 1,033 sampling reservoirs. CONCLUSIONS: Insufficient treatment or regrowth is suggested by the observation that more than 17% of these treated potable water contained coliform. TC and FC positive samples appear to be similar and seasonally influenced in treated water. Two different periods must be considered for the occurrence of both TC and FC positive samples: (i) a warm-weather period (September-March) with high percentage of contaminated samples; and (ii) cold-weather period (April-August) were they are lower. Both TC and TF positive samples declined with the decreased of water temperature. OBJETIVO: Avaliar a qualidade microbiológica de amostras de água tratada e não-tratada proveniente de comunidades urbanas e rurais e examinar a relação entre ocorrência de coliformes e a média de temperatura da água, e uma comparação dos níveis de precipitação de chuva. MÉTODOS: No período de 1996 a 1999, foram analisadas 3.073 amostras de água tratada (clorada) e não-tratada pelo método dos tubos múltiplos para determinar o número mais provável de coliformes totais e fecais. Destas, 1.594 provenientes de água de torneiras, 1.033 de reservatório para estocar água tratada, 96 de água de minas e 350 de poços particulares. Tais amostras foram obtidas na região de Maringá, Paraná, Brasil. RESULTADOS: O maior número de amostras contaminadas por TC (coliformes totais) (83%) e FC (coliformes fecais) (48%) foi observado em água não tratada. O índice de TC e FC foi maior nas amostras de reservatórios do que nas torneiras ao longo de sistema de distribuição. Entre as amostras de água tratada, foram encontradas bactérias do grupo coliforme em 171 dos 1.033 reservatórios amostrados. CONCLUSÕES: A observação de que mais de 17% da água potável tratada contêm coliformes sugere tratamento insuficiente ou recrescimento. Em água tratada, amostras positivas para TC e FC parecem ser similares e sazonalmente influenciadas. Dois diferentes períodos podem ser considerados para a ocorrência de amostras positivas para TC e FC: (i) período quente e úmido (Setembro-Março) com alta percentagem de amostras contaminadas; e (ii) período frio e úmido (Abril-Agosto) onde a positividade é baixa. Amostras positivas para TC e FC diminuem com o decréscimo da temperatura da água.